DOI: 10.11606/d.100.2012.tde-09122012-114702
|View full text |Cite
|
Sign up to set email alerts
|

Consciência, participação e negociação: uma leitura psicopolítica do processo de produção do Plano de Manejo da APA Várzea do Rio Tietê

Abstract: Uma aventura como esta felizmente me aproximou de pessoas que muito ensinaram e que merecem o meu profundo agradecimento. Assim, agradeço... ... aos colegas de turma e professores do Programa de Pós-Graduação em Mudança Social e Participação Política. ... aos colegas do Grupo de Pesquisa em Psicologia Polícia, Políticas Públicas e Multiculturalismo (Gepsipolim). ... à equipe da Secretaria de Pós-graduação da EACH/USP, em especial ao Tiago Villa Mello. ... às equipes da Fundação Florestal e do Conselho Gestor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
1
0
3
Order By: Relevance
“…The sampling sites are in different hydrographic basins. The drainage of Colosso is via the rivers Preto da Eva and Urubu (Uatumã basin) while for Dimona drainage is to the Cuieiras river (Rio Negro basin) (Amazonas 2019; Costa et al 2023). In the Ducke Reserve (80 km away from the location of this study), there is also a difference in composition among various taxonomic groups, mainly trees, shrubs, lianas, birds, frogs, and sh.…”
Section: High Diversity and Site Effectmentioning
confidence: 99%
“…The sampling sites are in different hydrographic basins. The drainage of Colosso is via the rivers Preto da Eva and Urubu (Uatumã basin) while for Dimona drainage is to the Cuieiras river (Rio Negro basin) (Amazonas 2019; Costa et al 2023). In the Ducke Reserve (80 km away from the location of this study), there is also a difference in composition among various taxonomic groups, mainly trees, shrubs, lianas, birds, frogs, and sh.…”
Section: High Diversity and Site Effectmentioning
confidence: 99%
“…A inovação passa definitivamente por uma transformação no modo como se incorporam e reconhecem a novos atores como parte de processos até aqui centrados na figura do Estado. Processos de tomada de decisão e negociação necessitam gerar e aprofundar vínculos entre os múltiplos atores implicados e assumir que todos participam solidariamente da gestão do problema e dos processos inerentes a ele (Costa, 2012;Carmo & Silva, 2013;Tozato, Mello-Théry & Dubreuil, 2015).…”
Section: Ação Pública Movimentos Sociais E Direito à Cidadeunclassified
“…All community work aimed at engaging local actors requires a refined sociocultural reading 12 , 15 , 33 – 35 , with social leaders mapping, communication channels identification and means to favour community dialogue 12 , 34 . We identified that, as the territory is a live organism, the social compositions inherent to the space are fluid and are temporarily reorganised according to the experience; it is necessary that the engagement plan is able to be readjusted, maintaining the same values initially defined.…”
Section: Reflections On Wmp Brazil’s Community Engagement Experiencementioning
confidence: 99%